Management in peripheral arterial disease - Micker, Maciej; Chęciński, Paweł; Synowiec, Tomasz (Przewodnik Lekarza/Guide for GPs, 2006)
Peripheral arterial disease (PAD) is the chronic obstruction of the arteries supplying the lower extremities. PAD is a manifestation of systemic atherosclerosis that is associated with an increased risk of death and ischemic events that is myocardial infarction and cerebral stroke. Treatment of PAD is aimed at maintaining functional status, reducing ischemic symptoms and improving walking in patients with intermittent claudication. Invasive revascularization procedures can be considered for patients with critical limb ischemia or when medical therapy fails.